Cervical Thymic Cyst Mimicking Laryngocele. (17th December 2013) - Ozturk, Kayhan; Elsurer, Cagdas; Bulut, Serap; Duran, Mutlu; Ugras, Serdar
Abstract : Cervical thymic cysts are nearly 0.3% of all congenital cervical cysts. Thymic cysts are asymptomatic, but they rarely complain of dysphagia or tracheal obstruction symptoms. A soft, mobile, and painless mass increasing with valsalva maneuver directs the diagnosis of laryngocele. There has not been any study in the literature in which thymic cyst presenting like laryngocele. We hereby present a case of thymic cyst mimicking laryngocele that has not been reported so far.